Barbarism in Higher Education: Once Upon a Time in a University by Nhlanhla Maake - Mokubung Nkomo (Perspectives in Education, 2011)
From text: Barbarism in education? Sounds like a contradiction in terms. Barbarism in politics, though odious, has arguably become more conventional than in education. If true, it is a serious indictment indeed. Nhlanhla Maake’s memoir seeks to take the reader through a thicket of institutional practices that seem to be contrary to the spirit and letter of transformation at a particular university: as he experienced it. It is a gripping memoir of Maake’s ‘once upon a time in a university’ sojourn.